2023
DOI: 10.1002/art.42528
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of Pharmacologic NAD+ Boosting as a Promising Therapeutic Approach in Rheumatoid Arthritis

Abstract: ObjectiveWe analyzed NAD+ metabolism in patients with rheumatoid arthritis (RA), its association with disease activity and clinical outcomes of RA, and the therapeutic potential of pharmacologic NAD+ boosting.MethodsOur study included 253 participants. In the first cohort, comprising 153 RA patients and 56 healthy donors, we assessed NAD+ levels and NAD+‐related gene pathways. We analyzed 92 inflammatory molecules by proximity extension assay. In the second cohort, comprising 44 RA patients starting anti–tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Using pathway and enrichment analysis, we found that nicotinate and nicotinamide (NAD + ) metabolism (Figure 3A,B) was highly impacted by E2l treatment on RA-FLS, which depicts its close regulation with RA pathogenesis. Boosting NAD + metabolism has been identified as an anti-inflammatory strategy in treating RA patients [70]. In our analysis, we discovered that estradiol treatment in RA-FLS increased the concentration of NAD + and its associated metabolite, 1-MNA (Figure 3C,D), showing that therapeutic horizons of estrogen extend to the regulation of positive metabolic alterations in RA.…”
Section: Discussionmentioning
confidence: 69%
“…Using pathway and enrichment analysis, we found that nicotinate and nicotinamide (NAD + ) metabolism (Figure 3A,B) was highly impacted by E2l treatment on RA-FLS, which depicts its close regulation with RA pathogenesis. Boosting NAD + metabolism has been identified as an anti-inflammatory strategy in treating RA patients [70]. In our analysis, we discovered that estradiol treatment in RA-FLS increased the concentration of NAD + and its associated metabolite, 1-MNA (Figure 3C,D), showing that therapeutic horizons of estrogen extend to the regulation of positive metabolic alterations in RA.…”
Section: Discussionmentioning
confidence: 69%
“… 30 However, a recent study revealed that boosting NAMPT-NAD was beneficial for RA patients. 31 Meanwhile, SIRT1 expression is usually deficient in rheumatic subjects. As a result, SIRT1 up-regulation is taken as a feasible anti-rheumatic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found through the analysis of plasma samples that individuals with RA exhibit lower average levels of NAD+ and NADH metabolites than their healthy counterparts [78]. Additionally, a change in NAD+ metabolism has also been detected in RA patients, which is directly linked to the disease's inflammatory state, and can be reversed with anti-TNF therapy [78].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Recently, it has been found through the analysis of plasma samples that individuals with RA exhibit lower average levels of NAD+ and NADH metabolites than their healthy counterparts [78]. Additionally, a change in NAD+ metabolism has also been detected in RA patients, which is directly linked to the disease's inflammatory state, and can be reversed with anti-TNF therapy [78]. Furthermore, the potential of using NAD+ enhancers to restore NAD+ levels has been proposed as a potential new clinical strategy to combat inflammation in these patients [78] In this context, treatment with high doses of sustained NAM demonstrated a substantial benefit for RA patients [79,80]; however, its effect on gut permeability was not further studied.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%